Pemanfaataka Media Sosial Youtube Sebagai Media Pembelajaran Bahasa Indonesia di Era Digital - Muhammad Ryan; Jumadi Jumadi; Dwi Wahyu Candra Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
This research is motivated by the development of technology in the digital era, including social media, which has affected all aspects of life, one of which is the world of education. This development makes teachers try to create interesting learning media for students, so that learning becomes more interesting. This research uses a descriptive research method and a qualitative approach. The data obtained comes from secondary data sources and public data sources. Secondary data sources include data sources in journals and articles, while public data sources include publicly available data, video content. The results of this research provide several options for YouTube video content that can be used as a reference for entertainment learning media for students. This aims to attract students' interest in learning Indonesian.